Sanctions under GATT article XIX versus voluntary export restraints - Franz Peter Lang (Intereconomics, 1988)
Voluntary export restraints play a substantial part in international trade today. This article compares the effects such restraints have upon certain exporting countries with the effect of sanctions applied under Article XIX of the GATT. It is shown that the microeconomic protectionism analysis used as a basis for the current debate on the reform of the GATT is unable to provide a conclusive answer as to which variant of protectionism would be preferable from the exporting economies' point of view. The article also indicates the direction in which existing research shortcomings can be reduced.
Keywords: 330; Protectionism